2021
DOI: 10.1111/acer.14696
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast attenuates alcohol cue–elicited frontostriatal functional connectivity in alcohol use disorder

Abstract: Alcohol use disorder (AUD) is a highly prevalent chronic relapsing disorder (Grant et al., 2015); however, it is among the most undertreated health conditions (Carvalho et al., 2019), with only 7% of adults with AUD receiving treatment (Hasin et al., 2007). The Food and Drug Administration has approved only 4 pharmacotherapies for the treatment of AUD to date, and these medications are limited in efficacy (Ray et al., 2019). There is a great need to develop new and more effective treatments for AUD, with a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Pharmacological manipulation may slightly change sensory processing and normalize attention distribution in AUD patients, followed by the transient off‐medication period, probably due to the delayed onset of drug action and maintenance (Chen & Skolnick, 2007 ). Our findings are in line with evidence from imaging studies indicating that detoxification treatment can influence neural activation and functional connectivity in patients with AUD (Burnette et al, 2021 ; Lukas et al, 2013 ; Vollstadt‐Klein et al, 2019 ). Previous functional MRI studies have indicated improved supramarginal gyrus activity in AUD patients in the emotional faces task after receiving nalmefene (Vollstadt‐Klein et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pharmacological manipulation may slightly change sensory processing and normalize attention distribution in AUD patients, followed by the transient off‐medication period, probably due to the delayed onset of drug action and maintenance (Chen & Skolnick, 2007 ). Our findings are in line with evidence from imaging studies indicating that detoxification treatment can influence neural activation and functional connectivity in patients with AUD (Burnette et al, 2021 ; Lukas et al, 2013 ; Vollstadt‐Klein et al, 2019 ). Previous functional MRI studies have indicated improved supramarginal gyrus activity in AUD patients in the emotional faces task after receiving nalmefene (Vollstadt‐Klein et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence has shown that detoxification treatment, even on an acute time scale, contributes to the normalization of brain function and structure in patients with AUD (Burnette et al, 2021 ; George et al, 2008 ; Lukas et al, 2013 ; Son et al, 2015 ; Vollstadt‐Klein et al, 2019 ; Wang et al, 2018 ). To explore the potential effects of medication on the MID‐related brain response, it is better to directly compare treated patients with treatment‐naïve individuals or perform pretreatment and posttreatment comparisons or treatment‐placebo comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies suggest that the PDE system is associated with downregulation of drug-seeking behaviours across opioids, alcohol and psychostimulants 35 . Notably, The PDE4B antagonist, ibudilast, has been shown to reduce heavy drinking among patients with AUD 36,37 and also shown to reduce inflammation in methamphetamine use disorder 38 , and was significant in our drug repurposing analysis. The top 20 correlations are annotated; all results can be found in the Supplementary Results.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, ibudilast improved mood during exposure to alcohol and stress cues, and reduced the mood-altering and stimulant effects of alcohol among participants with more severe depressive symptoms [ 192 ]. Another recent 2-week RCT enrolling 52 participants found that ibudilast also significantly decreased the odds of heavy drinking during the trial by 45% compared to placebo and attenuated neural response to alcohol cues in the ventral striatum [ 193 , 194 ].…”
Section: Pharmacological Treatments For Audmentioning
confidence: 99%